Perceived Problems of Strike Action and Deviant Behavior at Selected Higher Institutions in Ekiti State, Nigeria - Yusuf Suleiman; Muraina Kamilu Olanrewaju; Jamiu Mahmood Suleiman (Indonesian Journal of Educational Counseling, 2019)
This study aimed to investigate the perceived problems of strike action and deviant behavior in selected higher institutions in Ekiti State, Nigeria. The descriptive research design of ex-post-facto type was used in the study. Three hundred respondents were selected randomly from two Universities. The respondents were measured with a self-developed scale, and the data obtained were analyzed using descriptive (mean) statistical analysis. Four research questions were raised and answered. The result showed that causes of strike action in selected higher institutions include non-payment of teacher’s salaries, low responds to problems confronting schools among others, problems of strike action in selected higher institutions include production of half-baked graduates, youth involvement in secret cult, widespread of examination malpractice, causes of deviant behavior in selected higher institutions include parental neglect, drug addiction, high level of poverty among others and problems of deviant behavior in selected higher institutions include incessant strike action, widespread of examination malpractice, prevalence of teenage pregnancy among others. Given these findings, the study recommended that school counselors should identify deviant behaviors and counsel adolescents on how it can be prevented and that Government should deem it fit to respond to the yearnings and aspirations of the workers in terms of quick payment of their salaries and other emoluments.